Multi-Target and Multi-Session Transcranial Direct Current Stimulation in Patients With Prolonged Disorders of Consciousness: A Controlled Study - Zhang, Xu; Liu, Baohu; Li, Yuanyuan; Duan, Guoping; Hou, Jun; Wu, Dongyu (Frontiers in Neuroscience, 2021)
Objectives: To investigate the effect of multi-session transcranial direct current stimulation (tDCS) over the prefrontal area, left dorsolateral prefrontal cortex (DLPFC), and bilateral fronto-temporo-parietal cortices (FTPCs) in patients with prolonged disorders of consciousness (DOC) and to examine the altered cortical interconnections using nonlinear electroencephalography (EEG). Methods: In this open-label controlled study, conventional treatments were implemented in both the control and tDCS groups, together with 80 tDCS sessions only in the tDCS group. The order of tDCS targets was as follows: prefrontal area, left FTPC, right FTPC, and left DLPFC. The Coma Recovery Scale-Revised (CRS-R) and nonlinear EEG index were evaluated before and after the treatment. Additionally, the modified Glasgow Outcome Scale (mGOS) was used as a follow-up evaluation at 12 months after the disease onset. Results: The CRS-R improved significantly in both groups after the treatment. However, the CRS-R and mGOS were more signiﬁcantly improved in the tDCS group than in the control group. Among the cross approximate entropy indices, the local CA-PA and CA-FA under the affected painful stimulus condition and all local and remote indices of the unaffected side under the unaffected painful stimulus condition were significantly higher in the tDCS group than in the control group. Multivariate logistic regression analysis revealed that group and type were the main relevant factors based on mGOS improvement. Multivariate linear regression analysis revealed that group, CA-FA, and CU-MTU were the main relevant factors based on CRS-R improvement under the affected painful stimulus conditions, whereas only CU-MTU and CU-FPU were relevant under the unaffected painful stimulus condition. Conclusions: Multi-target and multi-session tDCS could improve the cortical connections between the primary sensorimotor and frontal cortices of the affected hemisphere and the prefrontal-parietal and temporo-parietal associative cortical networks of the unaffected hemisphere. Thus, this tDCS protocol may be used as an add-on treatment for prolonged DOC.